ANALISIS MAKNA DAN FUNGSI SUFIKS DALAM NOVEL “DIARY CINTA” KARYA TIA LESTARI SIDABUTAR - Juni Agus Simaremare; Evin Rohmahaldo Purba; Francisco Simanjuntak; Hotmaida Lumbangaol; Sari Lumban Batu; Tio Hotma Hutauruk (Universitas Batanghari, 2025)
This research aims to analyze the use of suffixes in the novel